PENGARUH METODE DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP N 43 MERANGIN - Ahde Fitri (Pendidikan Matematika | STKIP YM Bangko, 2022)
This study aims to describe mathematical problem solving skills using the Discovery Learning method which is better than conventional learning on algebraic material for class VIII SMP N 43 Merangin Academic Year 2020/2021. Sampling using simple random sampling. The data analysis technique used to test the hypothesis is the t-test. From the analysis of the final test data in the experimental class obtained an average of 50.25 while the control class obtained an average of 34.248. The results of hypothesis testing are obtained, t count = 7,260 and t table = 1,685. Because t hitung > t tabel then H0 is rejected and H1 is accepted. The conclusion of this study is that the mathematical problem solving ability of class VIII SMP N 43 Merangin students using the Discovery Learning Method is better than the mathematical problem solving abilities of students taught by conventional learning in the 2020/2021 school year